Application of serological tests to assess the efficacy of foot-and-mouth disease vaccination in dairy cattle with or without viral leucosis - Capozzo, Alejandra Victoria (2018)
Enzootic bovine leucosis is an infectious viral disease of cattle distributed worldwide that affect dairy cattle over 2 years of age. This disease produces changes in the animal´s immune system that may affect vaccine efficacy. During the last 10 years many reports have highlighted the association of BLV infection with a diminished or modified immune response against routinely used cattle vaccines. Our group has focused on studying the possible role of BLV infection on the immune response elicited by foot-and-mouth disease primo or multiple vaccinations making use of serological assays aimed to characterize the antibody response in terms of IgG-subtypes and avidity. These tools demonstrated to be very useful for analyzing the effects of BLV in FMD vaccine immunity. The use of simple high-throughput assays delving on the quality of the antibody response is paramount for assessing vaccine efficacy and can help in analyzing the impact of BLV infection at herd level.